Estratigrafia de sequências de alta resolução e evolução paleoambiental dos carbonatos de Água Rasa da Formação Lagoa do Jacaré (Ediacaranocambriano), Grupo Bambuí, Brasil-MG - Samuel Amaral Moura Silva (2021)
The present study carried out a high-resolution stratigraphic and paleoenvironmental analysis of microbial carbonates from the Lagoa do Jacaré Formation (Bambuí Group). Two areas were selected: Ubaí (North of Minas Gerais) and Cordisburgo (central Minas Gerais state). The Bambui Group was an Ediacaran-Cambrian foreland basin in which sedimentation was a diachronic response to Brasilia orogen (west) and Araçuaí orogen (east). The detailed stratigraphic survey (1:20) and the study of sedimentary facies in Ubaí-MG, on the Januária paleo-high, allow us to detail 41 meters of a tidal flat depositional system having 16 different lithofacies, grouped into three diagnostic facies associations: 1) supratidal; 2) intertidal; 3) subtidal. The Cordisburgo record, on the Sete Lagoas paleo-high, is 27 meters-thickand represent an island-barrier depositional system. There are 11 lithofacies in the island-barrier system grouped into three diagnostic lithofacies associations: 1) Back Shoal; 2) Shoal 3) Shoal Front. The high-resolution stratigraphic approach allowed us to identify transgressive and regressive cycles (T-R) of different orders and to infer short-term and long-term fluctuations of the sea level during the deposition. Therefore, it enables a better understanding of the paleoenvironmental evolution of the studied records. In Ubaí area, the premise that the thickness of the tidal cycle is proportional to sea-level fluctuations allowed a semiquantitative analysis. In both depositional systems, tidal action was a crucial depositional process. The metric tidal ranges in Ubaí, and the herringbone cross-stratification in pebble grainstones, in Cordisburgo, suggest strong tidal currents, different from modern giant enclosed sea analogs, where tidal ranges are less than a few decimeters. Thus, based on sedimentologic and stratigraphic data, we suggest that the shallow-water carbonates from the Lagoa do Jacaré Formation were deposited on a semi-enclosed epicontinental sea subjected to strong tidal forces. In light of this, a partial reopening of the Bambuí Basin after a period of restriction probably occurred during the Lagoa do Jacaré Formation deposition, as previously suggested by isotopic data and now by field data.